LOW CONVICTION RATES IN CRIMES AGAINST WOMEN: ANALYZING PAKISTAN’S INVESTIGATIVE CHALLENGES - Qayyum Gondal, Abdul; Hatta, Zulkarnan; Ahmad, Matloob (Journal of Learning on History and Social Sciences, 2024)
Objective: This study examines the low conviction rates in Violence Against Women (VAW) cases in Pakistan, highlighting systemic, social, and legal challenges undermining justice delivery. Method: A qualitative approach was used to analyze legal, social, and institutional factors affecting conviction rates. Fieldwork conducted in Gujranwala, Pakistan (January–April 2023), gathered insights from law enforcement, prosecutors, and victims to capture the complexities of the criminal justice process. Results: The findings reveal systemic flaws, including outdated investigation protocols, insufficient forensic tools, and pervasive corruption. Patriarchal norms, judicial delays, and limited victim protection services exacerbate the issue. Institutional inefficiencies, such as untrained police officers and inadequate coordination among stakeholders, weaken prosecutions, while legal loopholes in Qisas and Diyat laws allow offenders to evade justice. Novelty: This study underscores the interplay between cultural norms and institutional inadequacies in perpetuating low conviction rates for VAW in Pakistan. It provides comparative insights with neighboring countries and proposes reforms to modernize investigation procedures and strengthen victim support mechanisms.